PENGGUNAAN ROLE PLAY UNTUK MENINGKATKAN KEMAMPUAN SPEAKING SISWA SMP DI JOMBANG - Amanita Fatimatuzzahro (Universitas Pesantren Tinggi Darul Ulum Jombang, 2015)
Speaking ability is an important factor for people in learning a language, but there are many difficulties faced by the eighth grade students of SMP DU 1. There are lack of vocabulary, motivation, and self confidence. Besides, only 40% of 29 students (11) can pass the target score of KKM (75). Therefore the researcher used role play technique to solve the students’ problems and to improve the students’ speaking ability. There are three kinds of role play, but this research used multiple role play. This research used Classroom Action Research (CAR) based on Kemmis and McTaggart which consists of planning, acting, observing and reflecting. This research used descriptive analysis which is supported by the quantitative and qualitative data. The quantitative data obtained by analyzing the result of students’ achievement test. Then, the qualitative data obtained by analyzing from the result of observation as the students’ involvement. The finding of this research indicated that the implementation of role play technique was successful. From the result of test in cycle, it showed that 26 of the students or 89% of the 29 students could pass the target score. Besides, the result of observation showed that by using role play technique, the students were actively involved during teaching and learning process. However, the improvement of speaking skill through role play could be obtained when role play were conducted under the following situations :1)The role play consisted of small groups of students (each group ideally consisted of two or three students), 2)The explanation of the material and the direction of role play were slowly delivered, 3)The teacher gave role orientation because it made the students easier to understand the task, 4) The students brought their dictionary to help them translate the expressions. Key words : Speaking, Teaching speaking, Role play, Multiple role play.